PERANCANGAN LANSKAP PETERNAKAN RUMINANSIA KECIL SEBAGAI SARANA AGROEDUTOURISM DI KAMPUS DRAMAGA INSTITUT PERTANIAN BOGOR - Arawinda Sahawidhiwidana; Akhmad Arifin Hadi (Jurnal Lanskap Indonesia, 2014)
The environmental conditions is a factors affecting of livestock directly or indirectly. The field laboratory of small ruminants is a kind of the IPB facilities. The condition of field laboratory has a less support of environment for these activities. Livestock productivity and optimal quality can indirectly support the livestock farming activities (educational and breeding). In addition, to support and develop the field laboratory of small ruminant as agroedutourism tourist activities. The objectives of this study are to identify the potency and problem of the site as an object to support agroedutourism and also designing ruminant’s landscape in developing and supporting the agroedutourism in IPB. This research uses descriptive method, survey method to data collection, and refers to the stages of the work made by Booth (1983). The results of this research is the design landscape of the animal husbandry environment to supports educational activities and agroedutourism with consider amenities of user and animals that are there. The Field Laboratory Small Ruminant is determined by six zone. They are, welcome area 912.2 m² (4.5%), service 1 035.6 m² (5.2%), buffer 8 899.5 m² (44.3%), tourism, educational, and livestock farming area is 9 245.6 m² (46%). Landscape design of small ruminants laboratory can function properly in the future for agroedutourism activity